IL-6 and IL-10 Levels, Rather Than Viral Load and Neutralizing Antibody Titers, Determine the Fate of Patients With Severe Fever With Thrombocytopenia Syndrome Virus Infection in South Korea - Yoo, Jeong Rae; Kim, Tae-Jin; Heo, Sang Taek; Hwang, Kyung-Ah; Oh, Hyunjoo; Ha, TaeHong; Ko, Hye Kyung; Baek, Seungjae; Kim, Ju Eun; Kim, Jun Hyeong; Lee, Jiin; Kang, Min Ji; et al. (Frontiers in Immunology, 2021)
Severe fever with thrombocytopenia syndrome (SFTS) is a new tick-borne viral disease, and most SFTS virus (SFTSV) infections occur via bites from the tick Haemaphysalis longicornis; however, SFTSV transmission can also occur through close contact with an infected patient. SFTS is characterized by acute high fever, thrombocytopenia, leukopenia, elevated serum hepatic enzyme levels, gastrointestinal symptoms, and multiorgan failure and has a 16.2 to 30% mortality rate. In this study, we found that age, dyspnea rates, aspartate aminotransferase (AST), alanine aminotransferase (ALT), lactate dehydrogenase, multiorgan dysfunction score (MODS), viral load, IL-6 levels, and IL-10 levels were higher in patients with fatal disease than in patients with nonfatal disease during the initial clinical course of SFTS. In addition, we found that IL-6 and IL-10 levels, rather than viral load and neutralizing antibody titers, in patients with an SFTSV infection strongly correlated with outcomes (for severe disease with an ultimate outcome of recovery or death).